2012
DOI: 10.1299/jpes.6.241
|View full text |Cite
|
Sign up to set email alerts
|

Development of PIRT and Assessment Matrix for Verification and Validation of Sodium Fire Analysis Codes

Abstract: Thermodynamic consequence in liquid sodium leak and fire accident is one of the important issues to be evaluated when considering the safety aspect of fast reactor plant building. The authors are therefore initiating systematic verification and validation (V&V) activity to assure and demonstrate the reliability of numerical simulation tool for sodium fire analysis. The V&V activity is in progress with the main focuses on already developed sodium fire analysis codes SPHINCS and AQUA-SF. The events to be evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…According to the research of Sandia National Laboratory (SNL) on sodium spray fire accident phenomenon identification and ranking table, it is found that the prediction of droplet size distribution is very important in sodium spray dynamics (Olivier et al, 2010). However, there is still a lack of relevant physical phenomena, and the empirical model is also lack of experiment verification (Ohno et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…According to the research of Sandia National Laboratory (SNL) on sodium spray fire accident phenomenon identification and ranking table, it is found that the prediction of droplet size distribution is very important in sodium spray dynamics (Olivier et al, 2010). However, there is still a lack of relevant physical phenomena, and the empirical model is also lack of experiment verification (Ohno et al, 2012).…”
Section: Introductionmentioning
confidence: 99%